Evidence-Based Challenges to the Continued Recommendation and Use of Peroxidatively-Susceptible Polyunsaturated Fatty Acid-Rich Culinary Oils for High-Temperature Frying Practises: Experimental Revelations Focused on Toxic Aldehydic Lipid Oxidation Products - Grootveld, Martin (Frontiers in Nutrition, 2022)
In this manuscript, a series of 110 research reports focused on dietary lipid oxidation products (LOPs), their toxicities and adverse health effects are critically reviewed in order to present a challenge to the mindset supporting, or strongly supporting, the notion that polyunsaturated fatty acid-laden frying oils are ‘safe’ to use for high-temperature frying practices. The generation, physiological fates and toxicities of less commonly known or documented LOPs, such as epoxy-fatty acids, are also considered. Primarily, an introduction to the sequential autocatalytic peroxidative degradation of unsaturated fatty acids (UFAs) occurring during frying episodes is described, as are the potential adverse health effects posed by the ingestion of aldehydic and other LOP toxins formed. In continuance, statistics on the dietary consumption of fried foods by humans are reviewed, with a special consideration of French fries. Subsequently, estimates of human dietary aldehyde ingestion are critically explored, which unfortunately are limited to acrolein and other lower homologues such as acetaldehyde and formaldehyde. However, a full update on estimates of quantities derived from fried food sources is provided here. Further items reviewed include the biochemical reactivities, metabolism and volatilities of aldehydic LOPs (the latter of which is of critical importance regarding the adverse health effects mediated by the inhalation of cooking/frying oil fumes); their toxicological actions, including sections focussed on governmental health authority tolerable daily intakes, delivery methods and routes employed for assessing such effects in animal model systems, along with problems encountered with the Cramer classification of such toxins. The mutagenicities, genotoxicities and carcinogenic potential of aldehydes are then reviewed in some detail, and following this the physiological concentrations of aldehydes and their likely dietary sources are considered. Finally, conclusions from this study are drawn, with special reference to requirements for (1) the establishment of tolerable daily intake (TDI) values for a much wider range of aldehydic LOPs, and (2) the performance of future nutritional and epidemiological trials to explore associations between their dietary ingestion and the incidence and severity of chronic non-communicable diseases (NCDs).